(untitled) (Ex Chordis, 2023)
The aim of this paper is to analyse Tartiniana Seconda MR58a for violin and piano by Luigi Dallapiccola (1904-1975). The piece is on the topic of re-writing the instrumental Italian music, and it borrows its themes from the Sonata VII B.a1 by Giuseppe Tartini (1692-1770). Moreover, both Dallapiccola and Tartini were born in the same land. Dallapiccola uses counterpoint and serial techniques to re-write the tartinian themes, creating a violin line that shares many virtuosities with the original Sonata VII, and a piano line that is not a simple accompaniment, but linked to the first one. Our analysis is inspired by Sandro Perotti and his research tips about re-writings; moreover, the form, canons, harmonic syntax and motivic elements are alnalysed, with some diagrams to resume the mathematical constructions of Dallapiccola’s writing.